Social Criticism in Wayang Kulit Purwa Performance by Purbo Asmoro, Study of Interpretation (Sanggit) and Treatment (Garap) - Nugroho, Sugeng (Harmonia: Journal of Arts Research and Education, 2023)
This study intends to examine wayang kulit purwa performances [from Central Java] of the plays Réyog Ponorogo and Sang Batara Sambo “Prahara Suralaya,” created by Purbo Asmoro (2022). Both of these works are fascinating to study because in addition to the fact that they are allusions to topical conflicts [in Indonesia] presented in the form of social commentary, the structure and texture of these performances differ from the treatment of wayang purwa performances in general. This problem is studied based on the ethnoart paradigm, using the Interpretation (Sanggit) and Treatment (Garap) Theories and critical analysis. Research data was collected through literature studies, documentation studies, and interviews. The results of the study show that the social criticism revealed in lakon Réyog Ponorogo is blatant, while the social criticism in lakon Sang Batara Sambo “Prahara Suralaya” as a whole is equivocal, but in the closing scene it is blatant. In creating a ‘new’ lakon, the dalang must master various references—both written and spoken—which will later be used as hipogram texts, interpret various hypogram texts into a story, and translate them into lakon wayang. The artistic ability of the dalang greatly influences the quality of wayang performances, the ability of the dalang to choose the elements of pakeliran treatment to be highlighted in each scene, the dalang’s ability to organize the performance supporting team, and the ability of the dalang to read the situation of the audience.